(untitled) (International Journal of Studies in Nursing, 2025)
Background: The COVID-19 pandemic disrupted clinical training for nursing students, leading to "reality shock" as they entered the workforce without sufficient hands-on experience. Design: This qualitative study employed a 120-minute focus group interview conducted in July 2022. Results: Nine senior nursing students from various educational institutions in Taiwan participated in the focus group interview. Most were female (88.9%) with an average age of 22. Thematic analysis revealed three major needs: (1) self-adjustment due to reduced clinical exposure, (2) more diverse, simulation-based teaching aligned with clinical realities, and (3) extended pre-employment training to compensate for practical skill gaps. Conclusion: The suspension of clinical placements during the pandemic left nursing students underprepared for professional practice. To support a smoother transition, nursing schools should adopt innovative, technology-enhanced teaching strategies, while hospitals must strengthen onboarding programs and mentorship. Addressing these gaps is essential to improving the readiness and retention of new nurses in the post-pandemic era. This study contributes insights into how educational and institutional support can be restructured to better equip students for professional nursing roles in crisis settings.